Zákon o registru smluv : komentář - Bouda, Petr; Fadrný, Martin, 1977-; Franc, Pavel, 1978-; Mazel, Filip (C.H. Beck, 2016)
Komentované znění zákona o registru smluv na základě stavu k 30. 6. 2016.
Keywords: registr smluv -- Česko; contracts register -- Czechia; zákony; komentáře; laws; commentaries